Double Roles of Macrophages in Human Neuroimmune Diseases and Their Animal Models - Xueli Fan; Hongliang Zhang; Yun Cheng; Xinmei Jiang; Jie Zhu; Tao Jin (Mediators of Inflammation)
Macrophages are important immune cells of the innate immune system that are involved in organ-specific homeostasis and contribute to both pathology and resolution of diseases including infections, cancer, obesity, atherosclerosis, and autoimmune disorders. Multiple lines of evidence point to macrophages as a remarkably heterogeneous cell type. Different phenotypes of macrophages exert either proinflammatory or anti-inflammatory roles depending on the cytokines and other mediators that they are exposed to in the local microenvironment. Proinflammatory macrophages secrete detrimental molecules to induce disease development, while anti-inflammatory macrophages produce beneficial mediators to promote disease recovery. The conversion of the phenotypes of macrophages can regulate the initiation, development, and recovery of autoimmune diseases. Human neuroimmune diseases majorly include multiple sclerosis (MS), neuromyelitis optica (NMO), myasthenia gravis (MG), and Guillain-Barré syndrome (GBS) and macrophages contribute to the pathogenesis of these neuroimmune diseases. In this review, we summarize the double roles of macrophage in neuroimmune diseases and their animal models to further explore the mechanisms of macrophages involved in the pathogenesis of these disorders, which may provide a potential therapeutic approach for these disorders in the future.